Working Situation and Research Willingness: A Case of Primary School Teachers in The Southeast of China - Gan, Huo-Hua (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2022)
Based on the pursuit of research-oriented teachers, this study temped to understand whether school teachers have the time, willingness, and demands to conduct research while teaching. A qualitative survey was conducted among primary school mathematics teachers in southern Fujian province, the Southeast of China, through Questionnaires Star, and 102 texts were obtained. The survey found that primary school mathematics teachers' average daily work time in the sample was about 10 hours. The work contents were cumbersome and diverse, including rigid and semi-rigid tasks, and a social control mode of short-term responsibility with limited personal autonomy was found. The lesson preparation adopted the modification and imitation mode, and the classroom teaching conducted preset adjustment orientation. The research awareness and innovation ability of lesson preparation and teaching were insufficient, but the overall willingness to do research was very high. Teaching-based empirical research was their favorite, aiming at improving personal, professional rank, and student achievement. The reasons for not wanting to do research were mainly busy work, lack of theoretical literacy, and expecting mentors to lead or team up with famous teachers. As such, some recommendations were put forward.